The acceptance of Digital Finance (DiFi) among Muslim consumers in Malaysia - Haneffa Muchlis Gazalia; Junisa Jumadi (Penerbit UMS, 2022)
Digital Finance (DiFi) is a promising way of promoting inclusive finance. The internet plays a significant role in promoting advancement in the financial industry, especially digital finance. There are many benefits digital finance could offer, such as greater financial inclusion, expansion of financial services, affordability, security, and convenience. Although there is an increasing number of digital finance adopters in recent years, the acceptance has not been impressive in rural areas. Many consumers in rural areas still seriously suffer from digital finance exclusion. The purpose of this study is to explore and understand the Muslim consumers' intention to use digital finance by extending the Technology Acceptance Model (TAM) with Perceived Credibility and Subjective Norm. A secondary methodology is used for this study through library research by reviewing the concepts of digital finance adoption. This conceptual paper provides an understanding of the acceptance of DiFi among Muslim consumers in Malaysia. The conceptual model of this study could contribute to researchers keen on investigating the adoption of DiFi relating to Muslim consumers. The factors presented in this study are limited. Future research should consider more measures of digital finance adoption. This paper is one of the very few attempts that examined the acceptance of digital finance among Muslim consumers in Malaysia.